2020
DOI: 10.36740/wlek202009103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Perioperative Nursing Care in the Satisfaction of Patients After Large Joint Replacements

Abstract: The medical services market is inevitably changing. Competition among health care institutions is growing, patients’ health awareness and expectations regarding the quality of health services are increasing. This translates directly into, among others, to the patient’s choice of medical facility. “Satisfaction” defined as “general satisfaction accompanying the consumption of products or services” is an important aspect affecting the position of a healthcare institution on the health services market. While in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Hygiene assistance was rated very positively by 76% of the respondents. Similar results were also obtained in another study aimed at the assessment of medical care, in which 53% of patients rated nursing care as very good, 43% as good, and 1% as bad [29]. Another study showed that providing information on the purpose and types of nursing procedures was rated positively by 78% of patients.…”
Section: Discussionsupporting
confidence: 80%
“…Hygiene assistance was rated very positively by 76% of the respondents. Similar results were also obtained in another study aimed at the assessment of medical care, in which 53% of patients rated nursing care as very good, 43% as good, and 1% as bad [29]. Another study showed that providing information on the purpose and types of nursing procedures was rated positively by 78% of patients.…”
Section: Discussionsupporting
confidence: 80%
“…Patients in the observation group received conventional treatment, including precautions, health education, postoperative basic maintenance, and discharge instructions. Patients in the experimental group received targeted treatment, including preoperative, intraoperative, and postoperative management [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…In evaluating a medical service, a particularly important aspect is the direct relationship between the medical staff and the patient. Along with this, the availability of a doctor, medical care, conditions in the ward, and the patient's involvement in the treatment process, all offer clear information as well as an improved state of health [58]. Preoperative diagnosis, location of surgery, and length of stay do not significantly affect hospital or clinician satisfaction [59].…”
Section: Practices For Evaluation Of Medical Servicesmentioning
confidence: 99%